The association between grandparents as caregivers and overdose mortality in Appalachia and non-Appalachia counties - Beatty, Kate E.; Mathis, Stephanie M.; McCurry, Abby R.; Francisco, Margaret M.; Meit, Michael; Wahlquist, Amy E. (Frontiers in Public Health, 2023)
Objective. To assess the association of drug overdose mortality with grandparents serving as caregivers of children in Appalachia and non-Appalachia in the U.S. Methods. This study used a cross-sectional design, with percent of grandparents as caregivers and overdose mortality rates being of primary interest. County-level data were combined, and descriptive, bivariate, and multivariable statistics were applied. Multiple sociodemographic and geographic variables were included: median age of the population, percent of the population that is uninsured, percent of the population that is non-Hispanic white, teen birth rate, percent of high school dropouts, and rurality. Results. The percent of grandparents as caregivers increased as the overdose mortality rate increased (p< .01). For every 1% increase in the overdose mortality rate, the percent of grandparents as caregivers increased by 56% in Appalachian counties compared to 24% in non- Appalachian counties. After adjusting for sociodemographic characteristics, the interaction between overdose mortality and Appalachian versus non-Appalachian counties was no longer significant (p = .3). Conclusions. Counties with higher overdose mortality rates had greater rates of grandparents as caregivers, with Appalachian counties experiencing greater rates of grandparents as caregivers than non-Appalachian counties. Sociodemographic characteristics that are often more prevalent in Appalachia may be driving the observed differences. Policy implications. Policies and programs are needed to support grandparents providing caregiving for children impacted by substance use disorders including reform to federal child welfare financing to support children, parents, and grandparent caregivers such as kinship navigation, substance use treatment and prevention services, mental health services and in-home supports.